Sports medicine essentials : core concepts in athletic training & fitness instruction - Clover, Jim. 4 0 16; 5 (Australia ;;Clifton Park, NY : Thomson Delmar Learning, 2007)
A comprehensive overview of sports medicine that discusses careers in the field, athletic training, strength and conditioning specialists, ethical and legal considerations, physical fitness assessment, nutrition and weight management, physical conditioning, emergency preparedness, infection control, injuries, and other related topics.
Includes bibliographical references (p. 680-681) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Sports medicine.;Physical fitness.;Sports medicine.;Physical fitness.;Sports Medicine; 20; 2